1989
DOI: 10.1021/jf00086a002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of riboflavin in aqueous solution

Abstract: Wurzenberger, M.; Gorsch, W. Enzymic oxidation of linolenic acid to l,Z-5-octadien-3-ol, Z-2-Z-5-octadien-l-ol and 10-oxo-E-8decenoic acid by a protein fraction from mushroom. (Psalliota bis pora). Lipids 1986, 21, 261-266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Totani et al (1975) and Aoyama et al (1985) have reported that riboflavin had little antioxidant effect, but Ohama and Yagi (1969) and Terada (1975) have reported that riboflavin tetrabutyrate and riboflavin tetranicotinate do have antioxidant effects, which they attributed to the riboflavin portions. In an emulsion, riboflavin tetrabutyrate was strongly antioxidant; it also had a synergistic effect with tocopherol (Toyosaki et al, 1987a). In addition, our experiment here showed that riboflavin had an antioxidant effect on the autoxidation of methyl linoleate.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Totani et al (1975) and Aoyama et al (1985) have reported that riboflavin had little antioxidant effect, but Ohama and Yagi (1969) and Terada (1975) have reported that riboflavin tetrabutyrate and riboflavin tetranicotinate do have antioxidant effects, which they attributed to the riboflavin portions. In an emulsion, riboflavin tetrabutyrate was strongly antioxidant; it also had a synergistic effect with tocopherol (Toyosaki et al, 1987a). In addition, our experiment here showed that riboflavin had an antioxidant effect on the autoxidation of methyl linoleate.…”
Section: Resultssupporting
confidence: 54%
“…Riboflavin tetrabutyrate in the form of an emulsion has antioxidant effects (Toyosaki et al, 1987a). A milk serum fraction separated from raw cow milk by gel filtration, which may be a protein-bound riboflavin, is strongly antioxidant in vitro (Toyosaki et al, 1987b).…”
Section: Tlc Of Samplesmentioning
confidence: 99%
“…Indeed, vitamin C has been previously shown to efficiently deoxygenate graphene oxide in aqueous and organic dispersion [22]. In the present work, other hydrosoluble vitamins, namely vitamin B 6 (in two forms: pyridoxine and pyridoxamine dihydrochloride) [40,41] and vitamin B 2 [(-)riboflavin [42] and riboflavin 5'-monophosphate salt hydrate, the latter being a more soluble version of the former] were assayed. Also, the organic acids citric acid, fumaric acid, L-malic acid, and L-tartaric acid, all of which possess known antioxidant activity [43], were tested.…”
Section: Reduction Of Graphene Oxide With Biomoleculesmentioning
confidence: 97%
“…This indicates that these proteins are involved in the photolysis of riboflavin in milk. 126 The same degradation products were formed in both the model systems and the milk. 127 Analysis by GC-MS identified lumichrome as the major product of riboflavin photolysis in skimmed milk exposed to sunlight.…”
mentioning
confidence: 75%